Psychedelic Communitas: Intersubjective Experience During Psychedelic Group Sessions Predicts Enduring Changes in Psychological Wellbeing and Social Connectedness - Kettner, H.; Rosas, F. E.; Timmermann, C.; Kärtner, L.; Carhart-Harris, R. L.; Roseman, L. (Frontiers in Pharmacology, 2021)
Background. Recent years have seen a resurgence of research on the potential of psychedelic substances to treat addictive and mood disorders. Historically and contemporarily, psychedelic studies have emphasised the importance of contextual elements ('set and setting') in modulating acute drug effects, and ultimately, influencing long-term outcomes. Nevertheless, current small-scale clinical and laboratory studies have tended to bypass a ubiquitous contextual feature of naturalistic psychedelic use: its social dimension. This study introduces and psychometrically validates an adapted Communitas Scale, assessing acute relational experiences of perceived togetherness and shared humanity, in order to investigate psychosocial mechanisms pertinent to psychedelic ceremonies and retreats. Methods. In this observational, web-based survey study, participants (N = 886) were measured across five successive time-points: 2 weeks before, hours before, and the day after a psychedelic ceremony; as well as the day after, and 4 weeks after leaving the ceremony location. Demographics, psychological traits and state variables were assessed pre-ceremony, in addition to changes in psychological wellbeing and social connectedness from before to after the retreat, as primary outcomes. Using correlational and multiple regression (path) analyses, predictive relationships between psychosocial 'set and setting' variables, communitas, and long-term outcomes were explored. Results. The adapted Communitas Scale demonstrated substantial internal consistency (Cronbach's alpha = 0.92) and construct validity in comparison with validated measures of intra-subjective (visual, mystical, challenging experiences questionnaires) and inter-subjective (perceived emotional synchrony, identity fusion) experiences. Furthermore, communitas during ceremony was significantly correlated with increases in psychological wellbeing (r = 0.22), social connectedness (r = 0.25), and other salient mental health outcomes. Path analyses revealed that the effect of ceremony-communitas on long-term outcomes was fully mediated by communitas experienced in reference to the retreat overall, and that the extent of personal sharing or ‘self-disclosure’ contributed to this process. A positive relationship between participants and facilitators, and the perceived impact of emotional support, facilitated the emergence of communitas. Conclusions. Highlighting the importance of intersubjective experience, rapport, and emotional support for long-term outcomes of psychedelic use, this first quantitative examination of psychosocial factors in guided psychedelic settings is a significant step towards evidence-based benefit-maximisation guidelines for collective psychedelic use.